Familie şi societate în nord-vestul Transilvaniei (a doua jumătate a secolului XIX – începutul secolului XX) - Brie, Mircea (2008)
Abstract: The historical-demographic approach of family in their relationship with society with different transitory societal or community typologies is a complex initiative that needs a methodological approach including peripheral elements as well, besides a deep analysis on the central defining elements. The historical demography and other sciences, such as anthropology or history of mentalities, by directly or collaterally approaching the family, often make references to the three important moments in the individual’s life: birth, marriage and death. We have used several categories of documentary sources in our survey. We have the information on the population in north-western Romania due to the ecclesiastic notes (in the parish records or reports and the bishopric notes); on the other hand, we have the information provided by the Austrian and Austro-Hungarian state. Methodologically, the first phase of our research consisted of the preparation of the documents investigation strategy, as